2012
DOI: 10.1007/s11605-011-1811-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality Risk Score: Identification of Poor Outcomes Following Upfront Surgery for Resectable Pancreatic Cancer

Abstract: Background Identifying pancreatic cancer patients at high risk of early mortality following pancreaticoduodenectomy (PD) is important for treatment decisions in a multidisciplinary setting. This study examines the preoperative predictors of early mortality following PD and combines these variables into an early mortality risk score (EMRS). Methods Medical records of patients who underwent PD for pancreatic adenocarcinoma at the Johns Hopkins Hospital between 30 August 1993 and 28 February 2005 were reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 30 publications
3
63
1
Order By: Relevance
“…Secondly, besides overall health status, the presence of significant comorbidities and nutritional deficiency (18), understanding tumor biology may assist clinicians in selecting patients for surgery. No validated prognostic biomarkers predict recurrence following resection.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, besides overall health status, the presence of significant comorbidities and nutritional deficiency (18), understanding tumor biology may assist clinicians in selecting patients for surgery. No validated prognostic biomarkers predict recurrence following resection.…”
Section: Discussionmentioning
confidence: 99%
“…4 Significant predictors of 30day mortality included COPD, hypertension, neoadjuvant radiation therapy, elevated serum creatinine, and hypoalbuminemia. Japanese studies have demonstrated that risk factors for inhospital mortality were age, respiratory distress, activities of daily living within 30 days before surgery, angina, weight loss of more than 10%, American Society of Anesthesiologist class greater than 3, Brinkman index of more than 400, body mass index (BMI) of more than 25 kg/m 2 , white blood cell count of more than 11,000 cells/µL, platelet count of less than 120,000/µL, prothrombin time/international normal ized ratio of more than 1.1, activated partial thromboplastin time of more than 40 seconds, and serum creatinine levels of more than 3 mg/dL. 4 Male sex, emergency surgery, COPD, bleeding disorders, and blood urea nitrogen less than 8 mg/dL were independent variables in the 30day mortality group.…”
Section: Factors Associated With Postoperative Complicationsmentioning
confidence: 99%
“…The postoperative medical complication rate is 4%-19%. 2 Overall, the mortality risk due to pancreatic surgery is less than 5%. 3 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Centralization of pancreas surgery and advances in surgical techniques resulted in more patients being operated for advanced-staged tumours. 3,4 Patients with more comorbidity receiving pre-operative chemotherapy and/or vascular reconstructions in advanced disease, need more complex perioperative care.…”
Section: Introductionmentioning
confidence: 99%